Attenuation of visible and near-infrared light signals in murine cortical bone - Bittermann, Lennart Martin; Campbell, Graeme; Glueer, Claus-Christian; Schmalzl, Angelika (JOURNAL OF BONE AND MINERAL RESEARCH, 2019)
CRIS-Team WoS Importer:2020-02-07

Btn2a2 Regulates ILC2-T Cell Cross Talk in Type 2 Immune Responses - Frech, Michael; Omata, Yasunori; Schmalzl, Angelika; Wirtz, Stefan; Taher, Leila; Schett, Georg; Zaiss, Mario; Sarter, Kerstin (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) not only are responsible for shaping the innate immune response but also actively modulate T cell responses. However, the molecular processes regulating ILC-T cell interaction are not yet completely understood. The protein butyrophilin 2a2 (Btn2a2), a co-stimulatory molecule first identified on antigen-presenting cells, has a pivotal role in the maintenance of T cell homeostasis, but the main effector cell and the respective ligands remain elusive. We analyzed the role of Btn2a2 in the ILC-T cell cross talk. We found that the expression of Btn2a2 is upregulated in ILC2 following stimulation with IL-33/IL-25/TSLP. In vitro and in vivo experiments indicated that lack of Btn2a2 expression on ILC2 resulted in elevated T cell responses. We observed an enhanced proliferation of T cells as well as increased secretion of the type 2 cytokines IL-4/IL-5/IL-13 following cocultures with Btn2a2-deficient ILC2. In vivo transfer experiments confirmed the regulatory role of Btn2a2 on ILC2 as Btn2a2-deficient ILC2 induced stronger T cell responses and prevented chronic helminth infections. Taken together, we identified Btn2a2 as a significant player in the regulation of ILC2-T cell interactions.
CRIS-Team WoS Importer:2022-02-18

CCR8 Signaling via CCL1 Regulates Responses of Intestinal IFN-γ Producing Innate Lymphoid CelIs and Protects From Experimental Colitis - Kang, Le; Schmalzl, Angelika; Leupold, Tamara; Gonzalez-Acera, Miguel; Atreya, Raja; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Frontiers in Immunology, 2021)
A diverse spectrum of immune cells populates the intestinal mucosa reflecting the continuous stimulation by luminal antigens. In lesions of patients with inflammatory bowel disease, an aberrant inflammatory process is characterized by a very prominent infiltrate of activated immune cells producing cytokines and chemokines. These mediators perpetuate intestinal inflammation or may contribute to mucosal protection depending on the cellular context. In order to further characterize this complex immune cell network in intestinal inflammation, we investigated the contribution of the chemokine receptor CCR8 to development of colitis using a mouse model of experimental inflammation. We found that CCR8−/− mice compared to wildtype controls developed strong weight loss accompanied by increased histological and endoscopic signs of mucosal damage. Further experiments revealed that this gut protective function of CCR8 seems to be selectively mediated by the chemotactic ligand CCL1, which was particularly produced by intestinal macrophages during colitis. Moreover, we newly identified CCR8 expression on a subgroup of intestinal innate lymphoid cells producing IFN-γ and linked a functional CCL1/CCR8 axis with their abundance in the gut. Our data therefore suggest that this pathway supports tissue-specific ILC functions important for intestinal homeostasis. Modulation of this regulatory circuit may represent a new strategy to treat inflammatory bowel disease in humans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CCR8; chemokines; cytokines; inflammatory bowel disease; innate immunity; innate lymphoid cell

Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14

The role of IRF-1 during pathogen-induced intestinal Inflammation - Schmalzl, Angelika; Neurath, Markus; Wirtz, Stefan (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08